National immunization strategies targeting migrants in six European countries. Issue 32 (26th July 2019) - Giambi, Cristina; Del Manso, Martina; Dalla Zuanna, Teresa; Riccardo, Flavia; Bella, Antonino; Caporali, Maria Grazia; Baka, Agoritsa; Caks-Jager, Nuska; Melillo, Tanya; Mexia, Ricardo; Petrović, Goranka; Declich, Silvia; et al.
Highlights: Strategies for migrants immunization are in line with WHO and ECDC in the six countries. Individual data on immunized migrants are available at national level in two countries. Procedures to keep track of data on migrants immunization across countries are lacking. Abstract: Over the last three years an unprecedented flow of migrants arrived in Europe. There is evidence that vaccine preventable diseases have caused outbreaks in migrant holding centres. These outbreaks can be favored by a combination of factors including low immunization coverage, bad conditions that migrants face during their exhausting journey and overcrowding within holding facilities. In 2017, we conducted an online survey in Croatia, Greece, Italy, Malta, Portugal and Slovenia to explore the national immunization strategies targeting irregular migrants, refugees and asylum seekers. All countries stated that a national regulation supporting vaccination offer to migrants is available. Croatia, Italy, Portugal and Slovenia offer to migrant children and adolescents all vaccinations included in the National Immunization Plan; Greece and Malta offer only certain vaccinations, including those against diphtheria-tetanus-pertussis, poliomyelitis and measles-mumps-rubella. Croatia, Italy, Malta and Portugal also extend the vaccination offer to adults. All countries deliver vaccinations in holding centres and/or community health services, no one delivers vaccinations at entry site. Operating procedures that guarantee the migrants' access to vaccination at the community level are available only in Portugal. Data on administered vaccines is available at the national level in four countries: individual data in Malta and Croatia, aggregated data in Greece and Portugal. Data on vaccination uptake among migrants is available at national level only in Malta. Concluding, although diversified, strategies for migrant vaccination are in place in all the surveyed countries and generally in line with WHO and ECDC indications. Development of procedures to keep track of migrants' immunization data across countries, development of strategies to facilitate and monitor migrants' access to vaccinations at the community level and collection of data on vaccination uptake among migrants should be promoted to meet existing gaps.